SYNTHESIS OF THE THERMALLY COUPLED DISTILLATION SEQUENCES - E. А. Anokhina; А. V. Timoshenko (Тонкие химические технологии, 2017)
Approaching a hypothetical thermodynamically reversible process is one of the main directions of energy saving in distillation. In practice, this is achieved by the use of systems with coupled thermal and material flows (STMP). Such systems have long been used in the separation of zeotropic mixtures. As follows from the analysis of literature data, they save energy costs by up to 30%. Recently, it has been revealed that the use of such systems is possible, expedient and energetically advantageous for separating the close-boiling and azeotropic mixtures by extractive distillation (ED). The article considers the main approaches to the synthesis of distillation schemes, including systems with STMP: 1) a method based on the construction of a "superstructure"; 2) a method based on the concept of thermodynamically equivalent configurations; 3) an evolutionary algorithm; 4) a method based on the transformation of distillation scheme graphs. As the analysis of the literature has shown, the first three methods are sufficiently well developed only for the synthesis of distillation schemes with STMP to separate zeotropic mixtures. There are a relatively small number of publications that consider the generation of ED schemes with STMP based on the concept of thermodynamically equivalent configurations for distillation of specific binary mixtures. The only current system approach to the synthesis of ED schemes with coupled thermal and material flows for multicomponent mixtures is the method of graphs (algorithm 4). At present, the first step has been taken to implement it in the form of a computer program. Thus, the article presents the current state of the problem of synthesizing highly effective, energy-saving distillation technologies, including extractive distillation, based on the analysis of publications over the past 20-25 years.